Clinical guidelines for the diagnosis and treatment of patients with irritable bowel syndrome - V. T. Ivashkin; Ju. A. Shelygin; E. K. Baranskaja; E. A. Belousova; S. V. Vasil'ev; O. V. Golovenko; A. O. Golovenko; E. G. Grigor'ev; N. V. Kostenko; V. N. Kashnikov; V. F. Kulikovskij; T. L. Lapina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.